Jianpi Yiqi Busui prescription alleviates myasthenia gravis by regulating Th17 through the TAK1/P38 MAPK/eIF-4E signaling pathway - Zhuming Chen; Jing Lu; Tianying Chang; Dongmei Zhang; Yibin Zhang; Miao Liu; Tong Wu; Peng Xv; Jian Wang (Biomolecules & Biomedicine)
Jianpi Yiqi Busui Prescription (JYBP), a traditional Chinese medicine (TCM) formula, is used in the treatment of myasthenia gravis (MG). However, its mechanisms of action still require further clarification. In this study, an experimental autoimmune myasthenia gravis (EAMG) rat model was established for research. Changes in body weight, forelimb grip strength, Lennon clinical score, and antifatigue ability of EAMG model rats were recorded to evaluate the effectiveness of JYBP. Flow cytometry was utilized to count Th17, Th1, Th2, and Treg cells in lymphocytes. ELISA and RT-qPCR were used to measure acetylcholine receptor antibody (AChR-Ab) and Th17-related cytokines, including IL-17, IL-21, IL-23, TNF-α, TGF-β, IL-1β, and IL-6. Western blot and immunofluorescence staining were used to detect the expression levels of key proteins and their phosphorylated forms, such as transforming growth factor beta-activated kinase 1 (TAK1), P38 mitogen-activated protein kinase (P38 MAPK), and eukaryotic initiation factor 4E (eIF-4E). The results indicate that JYBP can increase the body weight of EAMG model rats, improve grip strength and antifatigue ability, and reduce the Lennon clinical score and AChR-Ab concentration. Mechanistic studies indicate that JYBP can inhibit the differentiation of CD4+ T cells into Th17 and Th1, promote their differentiation into Th2 and Treg, and regulate the expression of Th17-related cytokines. Further research shows that JYBP can reduce the expression of related proteins in the TAK1/P38 MAPK/eIF-4E signaling pathway. In conclusion, JYBP can alleviate the condition of EAMG model rats, positively affecting MG treatment. The inhibitory effect of JYBP on the differentiation of CD4+ T cells into Th17 may be related to the TAK1/P38 MAPK/eIF-4E signaling pathway.